2009
DOI: 10.1590/s0102-67202009000200006
|View full text |Cite
|
Sign up to set email alerts
|

Gastric volvulus: A review of 38 cases

Abstract: BACKGROUND: Gastric volvulus is frequently an asymptomatic disease, and it is usually diagnosed during radiographic examination of the superior digestive tract. The acute form, however, can spawn serious and lethal clinical consequences. This disease is defined by the anomalous rotation of the stomach over itself, and it can be classified according to type, extension, direction, etiology, and clinical presentation. AIM: To review the records from 38 patients with gastric volvulus diagnosed in the Hospital das … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
29
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 18 publications
2
29
0
3
Order By: Relevance
“…This patient was previously asymptomatic and reported no symptoms of volume reflux or regurgitation. In a review of 38 cases of gastric volvulus, Carlos et al 15 found 50% of patients to have been asymptomatic prior to acute presentation 16…”
Section: Discussionmentioning
confidence: 99%
“…This patient was previously asymptomatic and reported no symptoms of volume reflux or regurgitation. In a review of 38 cases of gastric volvulus, Carlos et al 15 found 50% of patients to have been asymptomatic prior to acute presentation 16…”
Section: Discussionmentioning
confidence: 99%
“…In primary gastric volvulus, the mechanism is attributed to laxity of the ligaments supporting the stomach, that is, the gastrocolic, gastrolienal, gastrohepatic and gastrophrenic ligaments. On the other hand, secondary gastric volvulus is more common and is caused by predisposing factors that facilitate rotation of the stomach such as hiatus hernia, traumatic diaphragmatic hernia, gastric tumours and ulcers, diaphragmatic eventration, phrenic nerve palsy and adhesions from other surgeries 1 6 7…”
Section: Discussionmentioning
confidence: 99%
“…The initial management for acute gastric volvulus includes resuscitation, placement of a nasogastric tube, gastric decompression and resting in the prone position 5 6. Emergency laparotomy is the option of choice to prevent complications such as strangulation, gangrene and perforation 2 4.…”
Section: Treatmentmentioning
confidence: 99%
“…In addition to ligament alterations, other aetiologies can be involved in volvulus genesis. Congenital or acquired (e.g., postoperative) adhesions or lesions (ulcers or tumours) can provide a basis for gastric rotation [4]. discomfort.…”
Section: Discussionmentioning
confidence: 99%